HUBUNGAN ASUPAN NUTRISI VITAMIN B6 DENGAN KARAKTERISTIK RESPONDEN DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Elan Virginia S. Nasution (Jurnal Kesehatan, 2024)
Background: Vitamin B6 (pyridoxine) is needed in several metabolic processes. The body needs vitamin B6 for the reactions of more than 100 enzymes, brain development during pregnancy, and immune function. Vitamin B6 deficiency can cause anemia, skin rashes, depression and a weak immune system. Objective: This study aims to analyze the frequency distribution of Vitamin B6 intake and see its relationship with other variables such as age, gender and BMI of the respondents studied. Method: The type of research used in this research is a quantitative descriptive method with a cross sectional design. The sampling technique used in this research was accidental sampling technique. Data collection was carried out by distributing SQ-FFQ (Semi Quantitativ- Food Frequency Questionnaire) questionnaires to 221 samples. Results: This study shows that there are respondents who have an abnormal frequency distribution of Vitamin B6 (68.3%). There is no relationship between gender and vitamin B6 intake (P- Value = 0.051), there is no relationship between age and vitamin B6 intake (P-Value = 0.389), and there is no relationship between BMI and vitamin B6 intake (P-Value = 0.789). Conclusion: There is no relationship between a person's age, gender and body mass index and the intake of vitamin B6 consumed.